Computer analysis of surface layers modified by chemical heat treatment - Barmin, A. E. (ISMA University of Applied Science, 2021)
Analysis of modern methods of research of microstructures of materials has been carried out. The possibility and evaluation of modern software for computer research tools in the processing of metallographic images is shown.
Keywords: metallography; chemical-thermal treatment; surface layers; microstructures